Association between time interval from neoadjuvant chemoradiotherapy to surgery and complete histological tumor response in esophageal and gastroesophageal junction cancer: a national cohort study. Issue 5 (2nd November 2019) - Klevebro, F; Nilsson, K; Lindblad, M; Ekman, S; Johansson, J; Lundell, L; Ndegwa, N; Hedberg, J; Nilsson, M
SUMMARY: The optimal time interval from neoadjuvant therapy to surgery in the treatment of esophageal cancer is not known. The aim of this study was to investigate if a prolonged interval between completed neoadjuvant chemoradiotherapy and surgery was associated with improved histological response rates and survival in a population-based national register cohort. The population-based cohort study included patients treated with neoadjuvant chemoradiotherapy and esophagectomy due to cancer in the esophagus or gastroesophageal junction. Patients were divided into two groups based on the median time from completed neoadjuvant treatment to surgery. The primary outcome was complete histological response. Secondary outcomes were lymph node tumor response, postoperative complications, R0 resection rate, 90-day mortality, and overall survival. In total, 643 patients were included, 344 (54%) patients underwent surgery within 49 days, and 299 (47%) after 50 days or longer. The groups were similar concerning baseline characteristics except for a higher clinical tumor stage ( P = 0.009) in the prolonged time to surgery group. There were no significant differences in complete histological response, R0 resection rate, postoperative complications, 90-day mortality, or overall survival. Adjusted odds ratio for ypT0 in the prolonged time to surgery group was 0.99 (95% confidence interval: 0.64–1.53). Complete histological response in the primary tumor (ypT0) was associated with significantly higher overall survival: adjusted hazard ratio: 0.55 (95% CI 0.41–0.76). If lymph node metastases were present in these patients, the survival was, however, significantly lower: adjusted hazard ratio for ypT0N1: 2.30 (95% CI 1.21–4.35). In this prospectively collected, nationwide cohort study of esophageal and junctional type 1 and 2 cancer patients, there were no associations between time to surgery and histological complete response, postoperative outcomes, or overall survival. The results suggest that it is safe for patients to postpone surgery at least 7 to 10 weeks after completed chemoradiotherapy, but no evidence was seen in favor of recommending a prolonged time to surgery after neoadjuvant chemoradiotherapy for esophageal cancer. A definitive answer to this question requires a randomized controlled trial of standard vs. prolonged time to surgery.